2022
DOI: 10.1111/jse.12930
|View full text |Cite
|
Sign up to set email alerts
|

Linalool: A ubiquitous floral volatile mediating the communication between plants and insects

Abstract: Terpenoids, one of the most important plant volatiles, mediate the communication between plants and pollinators, herbivores as well as pathogens. Recently, researchers have shown intensive interest in the complicated interactions. Linalool, an acyclic monoterpene, is one of the common flavor-related volatiles across the plant kingdom. In this review, we summarized the biosynthesis and transcriptional regulation of terpenoids, and then focused on the biological function of linalool in plant-insect interactions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 139 publications
0
7
0
Order By: Relevance
“…However, some degree of conservatism in the signals among related plants is needed so they would represent reliable cues to natural enemies of herbivores. Otherwise, the signals serving as indirect defenses may be too diverse to reliably convey the information (Zu et al, 2023). In contrast to direct defenses, high variation in VOC profiles between parental and hybrid plants can lead to a poorer parasitoid recruitment, and potentially worse indirect defense against specialized herbivores (Coll-Aráoz et al, 2020).…”
Section: Diversity In Indirect Defenses and Hybrid Performancementioning
confidence: 99%
“…However, some degree of conservatism in the signals among related plants is needed so they would represent reliable cues to natural enemies of herbivores. Otherwise, the signals serving as indirect defenses may be too diverse to reliably convey the information (Zu et al, 2023). In contrast to direct defenses, high variation in VOC profiles between parental and hybrid plants can lead to a poorer parasitoid recruitment, and potentially worse indirect defense against specialized herbivores (Coll-Aráoz et al, 2020).…”
Section: Diversity In Indirect Defenses and Hybrid Performancementioning
confidence: 99%
“…For example, linalool exists in nature in the form of two enantiomers which have entirely different functions. ( S )-(+)-linalool mainly attracts pollinators, and ( S )-(−)-linalool seems to have the effect of repelling insects [ 84 ].…”
Section: Development and Utilization Of Pest Attractants Based On Pvocsmentioning
confidence: 99%
“…Lianlool as a representative compound that exhibits obviously multifunctional characteristics actually exists as two enantiomeric isomers in nature, and both enantiomers occur randomly and disproportionately across plant species (Raguso, 2016). Based on the literature, Zhang et al (2022) summarized the biosynthesis and transcriptional regulation of terpenoids including Lianlool, and then focused on the biological function of linalool in plant–insect interactions. They found that flowers emitting linalool as the dominant volatile appeal to broad assemblages of pollinators, especially moths and bees are the main pollinators of Linalool‐ dominant flowers.…”
Section: Communication Factorsmentioning
confidence: 99%
“…(S)-(+)-Linalool mainly attracts pollinators, while (R)-(−)-Linalool seems to act as insect repellent. Thus, Zhang et al (2022) suggested that further research on the biofunctional diversity and genetic mechanisms behind linalool enantiomers could contribute to unveiling the complexity of plant survival strategies. Additionally, it could provide a theoretical foundation and practical basis for understanding the existence and directional transformation of enantiomeric isomers in plants.…”
Section: Communication Factorsmentioning
confidence: 99%
See 1 more Smart Citation